Gopay User Satisfaction Analysis in Semarang City during the Covid-19 Pandemic - Nugroho, Jati - (Admisi dan Bisnis, 2021)
This research was conducted to determine customer satisfaction of Gojek application users with the Go-Pay feature through e-service quality, perceived ease of use and perceived usefulness during the covid-19 pandemic. Respondents in this study were gopay users consists of students and workers in Semarang city with a sample of 100 respondents from the entire population. This study uses confirmatory factor analysis techniques and maximum likehood estimation on SEM (Structural Equations Modeling) from the statistical package AMOS 24.0 (Analysis of Moment Structure). The data collection technique used a questionnaire with a likert scale. The parameter estimation results are in accordance with the hypothesis that e-service quality significantly affects customer satisfaction with a critical ratio (c.r) of 4.177 and P-Value ***, as well as perceived ease of use has a positive effect on consumer satisfaction with a critical ratio (c.r) 3,471 and P-Value ***, also perceived usefulness have a positive effect on consumer satisfaction with a critical ratio (c.r) of 3,639 and P-Value ***. From this study it can be concluded that midst of the current Covid-19 pandemic consumers are still greatly helped by the gopay e-wallet feature. These benefits can be seen from the level of effectiveness and efficiency of prices, which through Gopay the costs incurred by consumers are cheaper than cash payments